Comparing the Phonological Performance of Kurdish and Persian EFL Learners in Pronunciation of English Vowels. (3rd August 2015) - Mirzaei, Khadijeh; Gowhary, Habib; Azizifar, Akbar; Esmaeili, Zakieh
Abstract: Knowing a second or foreign language is not possible without knowing its sound system. Besides, it is also impossible to disregard the effect of the first language sound system on the pronunciation of sounds of the second. The more these effects disappear, the more native like the learners sound. Accordingly, comparing the sound system of the two languages helps recognize the differences of the languages and sources of feasible errors the learners make which results in decrease the effects of the first language. Thus, this study tried to compare the performance of EFL Kurdish and Persian learners in acquisition of English vowels. In so doing, contrastive analysis hypothesis (CAH) was applied to compare the vowels of Kurdish and Persian with English. Furthermore, a total of 120 students take parted in the study to study any probable differences between the phonological performance of Kurdish and Persian EFL learners at elementary and advanced levels. The results showed some significant differences at the elementary level between the two groups of speakers, though this was not attested at advanced levels. EFL educators can use the results of this research in their pedagogical judgment makings.